The structural geometry, metamorphic and magmatic evolution of the Everest massif, Nepal and South Tibet - Searle, M; Simpson, R; Law, R; Parrish, R (2001)
Two large scale, low-angle, north-dipping normal faults cut through the Everest massif, both faults being part of the South Tibetan Detachment (STD) system bounding the top of the southward extruding High Himalayan crustal wedge (Searle, 1999). The lower fault, the Lhotse detachment (LD) separates sillimanite + cordierite gneisses, calc-silicates and amphibolites, intruded by numerous leucogranite sills and dykes below, from greenschist facies pelites and calc-silicates (Everest series) above. The fault has been folded around the ballooning sill of the Nuptse leucogranite, but truncates dykes in the footwall. The upper fault, the Qomolangma detachment (QD), separates the Everest series greenschists below from the unmetamorphosed Ordovician sediments above. On the SW face of Everest in Nepal, the greenschists are ca. 2000 m thick, but to the north, along the Rongbuk glacier in Tibet the two faults converge into one large shear zone. Kinematic indicators from footwall rocks show top-down-to-north shear sense during non-coaxial simple shear, but the low degree of fabric symmetry suggests an important contribution of pure shear flattening (coaxial) deformation. Stretching lineations consistently trend NNE. Early shearing at temperature greater than 450-500°C, as evidenced from plastically deformed feldspars, were followed by brittle faulting at higher structural levels. Along the Rongbuk valley laterally continuous leucogranite sheets are foliation-parallel and can be traced south to connect with the Pumori-Lingtren-Nuptse granite in Nepal. The Makalu-Chomolonzo leucogranites are also part of the same granitic sheet which extends all across this part of the High Himalaya, at least from Makalu to Cho Oyu. Monazites from the Everest granites have U-Pb ages between 20.5-21.3 Ma (Simpson et al., 2000). A few later narrow dykes cross-cut the foliation and monazites from these leucogranites have Th-Pb ages of 16.8 ± 0.8 and 16.4 ± 0.6 Ma (Murphy and Harrison, 1999). In Nepal all the leucogranites are restricted to the footwall of the Lhotse detachment and along the Rongbuk valley, only a few late cross-cutting dykes intrude into the higher levels beneath the Qomolangma detachment. No leucogranites cross-cut the QD indicating that the last brittle motion along the QD occurred after ≈ 16 Ma. Minimum horizontal offsets of dip-slip motion along the STD normal faults are greater than 70 km and probably exceed 100 km (North-South). Sillimanite + cordierite gneisses and leucogranite sills intruding them in the footwall of the STD have been exhumed from depths of around 17-20 km at least 70 km to the north beneath the Tibetan plateau.